Toxoplasma gondii seropositivity and substance use in US adults - Berrett, Andrew N; Gale, Shawn D; Erickson, Lance D; Thacker, Evan L; Brown, Bruce L; Hedges, Dawson W (Folia parasitologica, 2018)
The intracellular parasite Toxoplasma gondii (Nicolle et Manceaux, 1908) infects humans resulting in acute toxoplasmosis, an infection that in immunocompetent people is typically mild but results in persistent latent toxoplasmosis. In that T. gondii appears to affect dopamine synthesis and because addicting drugs affect midbrain dopamine transmission, latent toxoplasmosis could influence substance use. Using both the third and continuous National Health and Nutrition Examination Surveys from the US Centers for Disease Control and Prevention, we used logistic regression to test for associations between T. gondii seropositivity and subject self-report of having ever used tobacco, alcohol, marijuana, cocaine, heroin, or methamphetamine. In the third NHANES dataset, which included data for tobacco, alcohol, marijuana and cocaine, T. gondii seropositivity was associated with a reduced likelihood of self-reported marijuana (OR = 0.71 [95% CI: 0.58; 0.87]; p = 0.001) and cocaine use (OR = 0.72 [95% CI: 0.56; 0.91]; p = 0.006). In the continuous National Health and Nutrition Examination Surveys dataset, which included data for all six substances, T. gondii seropositivity was associated with a reduced likelihood of self-reported tobacco (OR = 0.87 [95% CI: 0.76; 1.00]; p = 0.044), marijuana (OR = 0.60 [95% CI: 0.50; 0.72]; p < 0.001), heroin (OR = 0.60 [95% CI: 0.42; 0.85]; p = 0.005) and methamphetamine use (OR = 0.54 [95% CI: 0.38; 0.77]; p = 0.001). We observed interactions between sex and T. gondii seropositivity in the prediction of self-reported use of tobacco and alcohol. Further, T. gondii seropositivity appeared to remove the protective effect of education and economic status against self-reported cigarette smoking. These findings suggest that T. gondii seropositivity may be inversely associated with some but not all types of substance use in US adults.
Keywords: Logistic Models; Young Adult; drug use; methamphetamine; Toxoplasma; Male; zpráva o sobě; Seroepidemiologic Studies; Risk Factors; séroepidemiologické studie; marijuana; mladý dospělý; centra pro kontrolu nemocí a prevenci (USA); výživa - přehledy; Adolescent; alcohol; Nutrition Surveys; Adult; prevalence; heroin; poruchy spojené s užíváním psychoaktivních látek; dospělí; toxoplazmóza; mužské pohlaví; senioři; Aged; mladiství; logistické modely; Centers for Disease Control and Prevention, U.S.; senioři nad 80 let; lidé; Toxoplasmosis; United States; ženské pohlaví; Humans; Self Report; rizikové faktory; Prevalence; Aged, 80 and over; Spojené státy americké; tobacco; Female; lidé středního věku; Substance-Related Disorders; cocaine; Middle Aged